Regret salience and accountability in the decoy effect - Terry Connolly; Jochen Reb; Edgar E. Kausel (Judgment and Decision Making, 2013)
Two experiments examined the impact on the decoy effect of making salient the possibility of post-decision regret, a manipulation that has been shown in several earlier studies to stimulate critical examination and improvement of decision process. Experiment 1 (N = 62) showed that making regret salient eliminated the decoy effect in a personal preference task. Experiment 2 (N = 242) replicated this finding for a different personal preference task and for a prediction task. It also replicated previous findings that external accountability demands do not reduce, and may exacerbate, the decoy effect. We interpret both effects in terms of decision justification, with different justification standards operating for different audiences. The decoy effect, in this account, turns on accepting a weak justification, which may be seen as adequate for an external audience or one's own inattentive self but inadequate under the more critical review triggered by making regret possibilities salient. Seeking justification to others (responding to accountability demands) thus maintains or exacerbates the decoy effect; seeking justification to oneself (responding to regret salience) reduces or eliminates it. The proposed mechanism provides a theoretical account both of the decoy effect itself and of how regret priming provides an effective debiasing procedure for it.